Ultrasound-Assisted Extraction of Phenolics and Antioxidants from Propolis for Stabilization of Sunflower Oil - Golmahi, Zeinab; Elhamirad, Amir Hossein (Revista de Ciencias Agrícolas, 2021)
Propolis is one of the byproducts of honey bees; it contains many phenolic compounds which are some of the most important natural antioxidants. The present study examined the antioxidant activity of propolis and its role in the stability of sunflower oil as a natural antioxidant in the form of Box–Behnken design. The extraction process was performed using an ultrasonic bath method with two factors in three levels which included 18 assays by the response surface methods. The investigated variables included the concentration of the extract (min: 30 and max: 1000 ppm), the extraction time (min: 10 and max: 30 minutes), and temperature (min: 37.5 and max: 50°C). After analysis of the data in optimal conditions, the concentration of propolis ethanol extract, extraction temperature, and extraction time was determined as 997.5 ppm, 34.6°C, and 30 min, respectively. In this condition, the total phenolic compounds and the free-radical scavenging properties were reported as 253.1mgGAE/100gDW and 85.9%, respectively. The result of the evaluation of the oxidative stability of the optimized sample oil showed reduced peroxide and thiobarbituric acid index compared to the control sample and synthetic antioxidants (BHT); also, the oil stability improved significantly over time.